Effects of Benson Relaxation Technique and Music Therapy on the Anxiety of Primiparous Women Prior to Cesarean Section: A Randomized Controlled Trial - Sedigheh Nosrati Abarghoee; Abbas Mardani; Robabe Baha; Nasrin Fadaee Aghdam; Mahboobeh Khajeh; Fatemeh Eskandari; Mojtaba Vaismoradi (Anesthesiology Research and Practice, 2022)
Background and Aims. Primiparous women experience high levels of anxiety before cesarean section. Therefore, this research aimed to investigate the effects of the Benson Relaxation Technique (BRT) and Music Therapy (MT) on the anxiety of primiparous women prior to cesarean section. Methods. A randomized controlled trial was carried out on 105 women scheduled for cesarean section. They were randomly assigned into three groups: BRT, MT, and control (n = 35 per group). The women in the BRT and MT groups performed exercises and listened to music, respectively, for 20 minutes prior to cesarean section. The State Anxiety Inventory was used to measure the women’s anxiety in the groups before and after the intervention. Results. Within-group comparisons showed that the women in the BRT (t = 5.61, p < 0.001, effect size (Cohen’s d) = 0.94) and MT (t = 3.83, p = 0.001, d = 0.64) groups had significantly lower anxiety after the interventions compared to before the interventions. Also, between-group comparisons revealed that anxiety after the intervention was significantly lower in the BRT and MT groups compared to the control group (p = 0.007). Conclusions. Although both of the BRT and MT helped with the reduction of anxiety among primiparous women before cesarean section, the BRT was shown more effective. These nonpharmacologic methods are safe and cost-effective and can improve well-being among women undergoing this invasive procedure. They can be used along with pharmacologic methods for reducing overreliance on medications.